Improving storage life of plantain and banana: IITA research guide, No. 62 - Shaun, R.; Ferris, R. (1997)
Plantain and banana are important food crops in the humid zone of sub-saharan Africa. A major problem of plantain and banana is that the fruits are highly perishable. Researchers, therefore, look for ways to extend storage life. Several methods can be used to extend storage life. The most important physiological functions affecting product quality during storage are respiration and transpiration,. To extend storage life, these functions should be reduced. This can be done by controlling temperature, humidity, ventilation, and atmospheric composition during storage. Chemical and physical treatment of fruits are other methods used to extend storage life. Postharvest handling processes can also be improved to extend storage life.